“The legislator does nothing in vain”: a note on Pol. IV.1 - Gonçalves de Sousa, Victor (Revista Archai, 2024)
In this paper, I intend to give some reasons for thinking that Aristotle holds the view that εὐδαιμονία not only provides the normative criterium that regulates the institution and reform of constitutions that fall short of the best one, but is also what is aimed at by the institution and reform of such constitutions, since, for Aristotle, the best constitution is just the constitution in which εὐδαιμονία can be maximally achieved (cf. Pol. VII.13 1332a4-7).